IMPROVING STUDENT’S SPEAKING SKILL BY USING CONVERSATION TEXT FOR STUDENTS AT ENGLISH HOUSE COURSE OF SMA NEGERI 10 KEPULAUAN TANIMBAR - Nurmalai, Laurentia Rini; Titirloloby, Piter; Luturmas, Jusuf (Technopreneurship and Educational Development Review (TENDER), 2024)
Education stands as a cornerstone sector, crucial for societal development and government attention, particularly in Indonesia. However, the education system in Indonesia faces challenges and necessitates continuous improvement to enhance learning and teaching processes. This study explores the effectiveness of utilizing conversation texts to improve students' speaking skills, focusing on English language learners at English House Course of SMA Negeri 10 Kepulauan Tanimbar. The research question addresses whether conversation texts can positively influence students' speaking proficiency. The objective is to assess the impact of incorporating conversation texts on students' speaking skills. This study employs descriptive and quantitative research methodologies with a sample population of 60 students. Pre-test and post-test assessments serve as research instruments, while data analysis utilizes the Product Correlation Moment technique and hypothesis testing with the t-test formula. The findings indicate a significant correlation between the use of conversation texts and the enhancement of students' speaking skills. The results demonstrate a strong correlation between the variables, with the t-test confirming the significance of the improvement. Thus, it is concluded that integrating conversation texts effectively improves students' speaking abilities at the English House Course of SMA Negeri 10 Kepulauan Tanimbar.